Profil Kawasan Reboisasi Mangrove Kepulauan Seribu Berdasarkan Karakteristik Lingkungan dan Fauna Makrobentik Terkait - Febrianti Lestari; Syahrial Syahrial; Rika Anggraini; Yudho Andika; Cut Meurah Nurul 'Akla; Agus Putra Abdul Samad (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Macrobenthic fauna is often used as a bioindicator of environmental quality. However, information about the environmental characteristics and the existence of macrobenthic fauna in the mangrove reforestation area is still very limited. The study of the profile of the Seribu Island mangrove reforestation area based on the characteristics of the macrobenthic environment and fauna was carried out in March 2014. The aim of this study is to determine the ecological conditions of the waters around the Seribu Island mangrove reforestation area. To find out the relationship between environmental characteristics and macrobenthic fauna with observation stations carried out by statistics on Correspondence Analysis (CA), while the environmental characteristics that determine macrobenthic fauna and their relationships are carried out with Principal Component Analysis (PCA) statistics and simple linear regression. The results of the study show that the concentration of measured environmental characteristics is not very different between stations and does not exceed the quality standard threshold for marine life. Then the macrobenthic fauna found consisted of 6 species with the highest density at Station 3 (05.00 ind/m2) and the lowest at Station 1 (02.00 ind/m2). At Station 1 the pH and temperature concentration is very high, while Station 2 and 3 have high salinity concentrations. Macrobenthic fauna Atilia (Columbella) scripta, Metopograpsus latifrons, Littoraria scabra, Saccostrea cucculata, and Cardisoma carnifex can be associated with mangroves at all stations. In addition, the environmental characteristics that determine the presence of C. carnifex macrobenthic fauna are pH parameters, where the higher the pH concentration, the lower the density of C. carnifex. Then the environmental characteristics that determine the presence of the macrobenthic fauna of S. cucculata, M. latifrons and A. scripta are determined by DO (Dissolved Oxygen) and salinity parameters namely the lower DO (Dissolved Oxygen) concentration and salinity, the higher the density of S. cucculata, M. latifrons and A. scripta.